2016
DOI: 10.1149/2.0141611jss
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—Growth of Layered WS2Electrocatalysts for Highly Efficient Hydrogen Production Reaction

Abstract: Seeking more economical alternative electrocatalysts without sacrificing much in performance to replace precious metal Pt is one of the major research topics in hydrogen evolution reactions (HER). Tungsten disulfide (WS 2 ) has been recognized as a promising substitute for Pt owing to its high efficiency and low-cost. Since most existing works adopt solution-synthesized WS 2 crystallites for HER, direct growth of WS 2 layered materials on conducting substrates should offer new opportunities. The future economy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…4a). [67][68][69] The binding energies of the WS2 doublet are in agreement with the semiconducting 2H or 3R phases of WS2, whereas the metallic 1T phase would result in lower binding energies. 3,[67][68][69] The WO3 content relative to the total W content, which likely originates from the oxidation of the films in air, was the lowest at 17% in the sample annealed at 400 °C, compared with 51% in the as-deposited film and 32 and 23%…”
Section: B Post-deposition Annealingsupporting
confidence: 65%
See 1 more Smart Citation
“…4a). [67][68][69] The binding energies of the WS2 doublet are in agreement with the semiconducting 2H or 3R phases of WS2, whereas the metallic 1T phase would result in lower binding energies. 3,[67][68][69] The WO3 content relative to the total W content, which likely originates from the oxidation of the films in air, was the lowest at 17% in the sample annealed at 400 °C, compared with 51% in the as-deposited film and 32 and 23%…”
Section: B Post-deposition Annealingsupporting
confidence: 65%
“…The S 2p region expectedly contained a doublet corresponding to S 2in WS2 with binding energies of 162.1 (S 2p3/2) and 163.3 eV (S 2p1/2) as shown in Figure 4b. [67][68][69][70] The broadening of the S 2p peak was attributed to the presence of substoichiometric WSz (z < 2) at binding energies of 161.2 and 162.4 eV and sulfur in oxysulfide or organic environment at 163.3 and 164.4 eV for the S 2p3/2 and S 2p1/2 levels, respectively. [68][69][70] The relative content of the WS2-bound sulfur to the total sulfur content increased with increasing annealing temperature from 47% in the as-deposited film to 68, 71, and 78 % in the films annealed at 300, 400, and 500 °C, respectively.…”
Section: B Post-deposition Annealingmentioning
confidence: 99%
“…This doublet corresponds to S 2− sulphur bonded in 2 H phase of WS 2 36 . Fortunately, the absence of S 2 2ligands peaks, which corresponds to the presence of WS 3 and oxidized sulphur species, is a good indicator that the film is stoichiometric for both substrates 37,38 . The peaks obtained from the WS 2 films on the sapphire are almost identical to films grown on SiO 2 /Si.…”
Section: Figurementioning
confidence: 99%
“…The band at 511 cm –1 is assigned to terminal S–S stretching of S 2 2– in WS 3 . 29 As the temperature increases to 400 °C, the band of WS 3 weakens, whereas two bands at 411 and 350 cm –1 , respectively, attributed to the A 1g vibration of S and the E 2g 1 vibration of W–S in WS 2 41 are observed. A weak band around 175 cm –1 can also be assigned to NiS.…”
Section: Resultsmentioning
confidence: 98%
“… 48 Martin et al 47 indicated that the S 2p XPS spectrum of WS 3 showed two overlapping doublets attributed to S 2 2– and S 2– in a 1:2 proportion. Alsabban et al 41 suggested that both WS 2 and WS 3 contained S 2– , but only WS 3 possessed S 2 2– . The percentage of S 2 2– in WLDS-300 is 3 times higher than that in WLDS-500, suggesting more WS 3 in the former, which is consistent with the Raman results.…”
Section: Resultsmentioning
confidence: 99%